The postcranial skeleton of monolophosaurus jiangi (dinosauria: Theropoda) from the Middle Jurassic of Xinjiang, China, and a review of Middle Jurassic Chinese theropods - Xi-Jin, Z; Benson, R; Brusatte, S; Currie, P (2010)
The Middle Jurassic was a critical time in the evolution of theropod dinosaurs, highlighted by the origination and radiation of the large-bodied and morphologically diverse Tetanurae. Middle Jurassic tetanurans are rare but have been described from Europe, South America and China. In particular, China has yielded a number of potential basal tetanurans, but these have received little detailed treatment in the literature. Here we redescribe the postcranial skeleton of one of the most complete Chinese Middle Jurassic theropods, Monolophosaurus. Several features confirm the tetanuran affinities of Monolophosaurus, but the possession of primitive traits such as a double-faceted pubic peduncle of the ilium and a hood-like supracetabular crest suggest a basal position within Tetanurae. This conflicts with most published cladistic analyses that place Monolophosaurus in a more derived position within Allosauroidea. We review the Middle Jurassic record of Chinese theropods and compare Monolophosaurus to other Middle Jurassic theropods globally. These comparisons sug est that Monolophosaurus and Chuandongocoelurus formed an endemic theropod clade limited to the Middle Jurassic of Asia. Other Middle Jurassic Chinese theropods deserve further study. Copyright © Cambridge University Press 2009.